Motivators and barriers to engagement with evidence-based practice among medical and dental trainees from the UK and Republic of Ireland: a national survey - Bosun Hong; Eoin Daniel O'Sullivan; Christin Henein; Christopher Mark Jones (BMJ Open)
Objectives To explore the extent to which doctors and dentists in training within the UK and Republic of Ireland (RoI) engage in and with evidence-based practice (EBP), and to identify motivators and barriers to them doing so.Design An observational, prepiloted web-based survey developed by a trainee-led focus group.Setting The survey instrument was disseminated to doctors and dentists in training within the UK and RoI during June 2017 via social media and through deaneries, Royal Colleges and specialty-specific mailing lists.Participants Data from 243 trainees were analysed; 188 doctors from 31 specialties and 55 dentists from 9 specialties. Responses were received from trainees at all stages of postgraduate training though the overall response rate was low.Primary and secondary outcome measures The motivators and barriers to, and the extent of, trainee engagement with EBP.Results Cronbach’s α was 0.83. Most trainees (87.6% (n=148) of doctors and 75.1% (n=39) of dentists) consulted the evidence base at least monthly, while 23.1% [n=39 doctors, 12 dentists] of both specialties did so daily. The two most commonly cited barriers to engagement with EBP for both doctors and dentists, respectively, were insufficient time (57.6% (n=95) and 45.1% (n=23)) and a tendency to follow departmental practice (40.6% (n=67) and 45.1% (n=23)). Key motivators for EBP included curiosity, following the example set by senior colleagues and a desire to avoid harm. Most trainees reported high levels of confidence interpreting evidence yet for 26.8% (n=45) of doctors and 36.5% (n=19) of dentists, medical hierarchy would impede them querying a colleague’s management plan based on their own reading of the evidence.Conclusions Time, accepted departmental practice and the behaviour of senior clinicians all highly impact on trainee engagement with EBP. Given the low response rate, the extent to which these data represent the overall population is unclear.